Peer-Based Education and Use of the SBIRT Model in Unique Settings with Transgender Young Adults. Issue 1 (3rd April 2019) - Dentato, Michael P.; Ortiz, Reyna; Orwat, John; Kelly, Brian L.; Gates, Trevor G.; Propper, Ellie
Abstract : Transgender young adults are at higher risk for alcohol and substance use that could lead to other health and mental health complications. Utilization of the Screening, Brief Intervention, and Referral to Treatment (SBIRT) model might be effective to identify members of this minority community at risk for alcohol and substance use, provide early interventions for those not meeting diagnostic criteria, and link them to care. A tailored, peer-based approach to universal screening with SBIRT could offer affirming experiences for transgender young adults to openly discuss substance use within unique practice settings such as the house/ball community. In addition to examining health and mental health challenges faced by transgender young adults, implications for the field of social work practice, research, and education are discussed related to utilization of SBIRT with this minority population, along with providing a relevant case scenario.